ANTIBACTERIAL COMPARISON BETWEEN MANUKA HONEY AND TUALANG HONEY AGAINST PORPHYROMONAS GINGIVALIS BACTERIA. - Veronica Septnina Primasari; Desy Fidyawati; Ike Nurmalisari Ramadhani (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Periodontal disease, namely gingivitis and periodontitis are an inflammatory condition of the periodontal tissue which involves interactions between bacteria, immune response, inflammatory reactions, and environmental factors. The main cause of periodontal disease is the proliferation of oral pathogenic biofilms. The main problems in the treatment of periodontal disease are antibiotic resistance and the side effects of using mouthwash which have increased over the last decades. Review: Manuka honey and tualang honey are popular ingredients and have antibacterial, antifungal, antioxidant, antiseptic and anti-inflammatory properties, which can be used as alternative choices. The purpose of this paper is to conduct an integrative literature study on manuka honey and tualang honey against the periodontal pathogenic bacteria, namely Porphyromonas gingivalis. The material analyzed was the antibacterial properties of manuka honey and tualang honey by comparing them based on the inhibition zone, MIC and MBC values. Conclusion: Manuka honey and tualang honey have antibacterial potential against Porphyromonas gingivalis, but manuka honey is more effective in inhibiting Porphyromonas gingivalis compared to tualang honey. Manuka honey and Tualang honey can be an alternative to avoid antibiotic resistance.